Dynamics and economic articulation of the county of Naviraí-MS in the context of regional geography sul-mato-grossense - Silva, Walter Guedes; Figueiredo Aguillera, Fernando (Geografares, 2019)
The aim of this article is to map and analyze the economic articulations of the geographic connection micropolis of the conty of Naviraí-MS in the context regional, national and international. As a methodological procedure, was adopted with basis for defining the regional, national and international articulations of counties listed on three indicators according to their characteristics: 1) capacity of self management; 2) capacity to sustain the territorial base; and 3) regional, national and international articulation capacity.